2016
DOI: 10.1080/09513590.2016.1232772
|View full text |Cite
|
Sign up to set email alerts
|

Local immunity status in patients with miscarriages and herpetic infection

Abstract: A study of the endometrium of women with herpetic infection has shown that early miscarriages (under 12 weeks) occurs as activation of cytotoxic natural killer (NK) cells with CD16 + phenotype and a pronounced suppression level of CD56 + cells endometrial type, and late miscarriages (13-22 weeks of gestation) occurs as cell deficit, followed by reduction of all CD8 + cytotoxic lymphocytes, and of CD56 + and CD16 + NK cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…Pregnancy loss in the early stages (up to 12 weeks) is manifested by activation of cytotoxic natural killers with CD16 þ phenotype and express suppression of the endometrial type level of CD56 þ cells, and in late stages (13-22 weeks of pregnancy) manifests a cellular deficiency, accompanied by a decrease in all cytotoxic lymphocytes -CD8þ, and natural CD56 þ and CD16 þ killers [6]. Analysis of endometrial cytotoxic lymphocytes levels depending on the form of pregnancy loss -spontaneous miscarriage and undeveloped pregnancy, with antenatal fetal death with its long delay in the uterine cavity.…”
Section: Research Findingsmentioning
confidence: 99%
“…Pregnancy loss in the early stages (up to 12 weeks) is manifested by activation of cytotoxic natural killers with CD16 þ phenotype and express suppression of the endometrial type level of CD56 þ cells, and in late stages (13-22 weeks of pregnancy) manifests a cellular deficiency, accompanied by a decrease in all cytotoxic lymphocytes -CD8þ, and natural CD56 þ and CD16 þ killers [6]. Analysis of endometrial cytotoxic lymphocytes levels depending on the form of pregnancy loss -spontaneous miscarriage and undeveloped pregnancy, with antenatal fetal death with its long delay in the uterine cavity.…”
Section: Research Findingsmentioning
confidence: 99%
“…A study of the endometrium of women with herpetic infection has shown that early miscarriages (under 12 weeks) occurs as activation of cytotoxic natural killer (NK) cells with CD16 + phenotype and a strong suppression level of CD56 + cells endometrial type, and late miscarriages (13-22 weeks of gestation) occurs as cell deficit, followed by reduction of all CD8 + cytotoxic lymphocytes, and of CD56 + and CD16 + NK cells (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Критерием тонкого эндометрия принято считать толщину эндометрия менее 7 мм и отсутствие трехслойной структуры в период «окна имплантации». Патофизиологические особенности тонкого эндометрия состоят в недостаточном росте железистого эпителия, обеднении сосудов и нарушении экспрессии ряда регуляторных цитокинов, ростовых факторов, натуральных киллеров, лимфоцитов, что в свою очередь, снижает имплантационную способность эмбрионов [3].…”
Section: ключевые слова: синдром тонкого эндометрия невынашивание беременности эндометрий цитотоксические лимфоциты эндометрия интерферонunclassified
“…Курманова 1,2 , Г.Ж. Анартаева 3 1. Научный центр акушерства, гинекологии и перинатологии, 2. Казахский Национальный университет им.…”
unclassified